Composite solid electrolyte membrane, preparation method thereof and battery
By using metal organic frame materials in the composite solid electrolyte membrane to define succinitrile inside its pores and forming a three-dimensional network structure, the problem of low conductivity of solid polymer electrolytes is solved, and the electrochemical performance and cyclic stability of the battery is significantly improved.
Patent Information
- Application Number
- CN202411898201.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The ionic conductivity of solid polymer electrolytes is low, mainly because Li transport within the polymer depends on the movement of the polymer segments, which are slow to move at room temperature.
By using metal organic frame materials in the preparation process of composite solid electrolyte membranes, succinidine molecules are limited inside their pores, reducing their plasticization effect on polymer segments, and by increasing the content of metal organic frame materials, a connected three-dimensional network structure is formed to improve conductivity.
The conductivity and mechanical properties of solid polymer electrolyte are improved, the reaction between succinitrile and lithium metal negative electrode is avoided, and the electrochemical performance and cycle stability of the battery are significantly improved.
Smart Images

Figure BDA0005202409160000101 
Figure BDA0005202409160000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a composite solid electrolyte membrane and a preparation method thereof and a battery. Background Art
[0002] Currently, lithium-ion batteries generally use liquid electrolytes, whose main components are flammable and volatile carbonate solvents. Solid-state batteries, due to the use of solid electrolytes, have better safety than liquid electrolytes and there is no risk of electrolyte leakage.
[0003] Solid polymer electrolytes have the potential to become the mainstream route for solid-state batteries due to their easy processing and low cost, but their ionic conductivity is usually low (σ RT <10 -4 This is mainly because the transport of Li in the polymer depends on the movement of polymer chains, which move slowly at room temperature.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The object of the present invention is to provide a composite solid electrolyte membrane and a preparation method thereof and a battery to solve or improve the above technical problems.
[0006] The present invention can be implemented like this:
[0007] In a first aspect, the present invention provides a method for preparing a composite solid electrolyte membrane, comprising the following steps: mixing a first lithium salt with polyethylene oxide to obtain an electrolyte;
[0008] The electrolyte and the filler are mixed, and then annealed and pressed into a film to obtain a composite solid electrolyte membrane;
[0009] The preparation of the filler comprises: mixing succinonitrile, a second lithium salt and a metal organic framework material under a vacuum environment and then performing ultrasonic treatment.
[0010] In an optional embodiment, the mass ratio of polyethylene oxide to the first lithium salt is 100:15 to 100:50;
[0011] And / or, the mass ratio of the electrolyte to the filler is 100:10 to 100:80.
[0012] In an alternative embodiment, the first lithium salt includes at least one of LiTFSI, LiFSI, LiClO4, LiBF4, LiPF6, LDFOB, and LiBOB.
[0013] In an optional embodiment, the annealing temperature is 50° C. to 80° C., and the annealing time is 5 h to 10 h.
[0014] In an optional embodiment, the pressing pressure is 0.1 MPa to 5.0 MPa.
[0015] In an optional embodiment, the second lithium salt includes at least one of LiTFSI, LiFSI, LiCIO4, LiBF4, LiPF6, LDFOB and LiBOB;
[0016] And / or, the metal organic framework material includes at least one of MOF-818 and MOF-919.
[0017] In an optional embodiment, the mass ratio of the second lithium salt to succinonitrile is 0.1:1 to 0.5:1;
[0018] And / or, the ratio of the total mass of succinonitrile and the second lithium salt to the mass of the metal organic framework material is 0.05:1 to 0.2:1.
[0019] In an optional embodiment, the temperature of the ultrasonic treatment is 60° C. to 200° C., and the time of the ultrasonic treatment is 0.1 h to 2 h.
[0020] In a second aspect, the present invention provides a composite solid electrolyte membrane prepared by the preparation method of any one of the aforementioned embodiments.
[0021] In an optional embodiment, the thickness of the composite solid electrolyte membrane is 30 μm to 100 μm.
[0022] In a third aspect, the present invention provides a battery comprising the composite solid electrolyte membrane of the aforementioned embodiment.
[0023] The beneficial effects of the present invention include:
[0024] In the process of preparing the composite solid electrolyte membrane, the present application first uses a metal organic framework material to confine the succinonitrile molecules inside its pores, so that the plasticizing effect of succinonitrile on the polymer chain segments is greatly reduced, which is beneficial to improving the mechanical properties of the polymer electrolyte. At the same time, as the content of the metal organic framework material increases, the metal organic framework material particles contact each other, prompting the succinonitrile in the pores of the metal organic framework material to form a connected three-dimensional network structure, so that the conductivity of the electrolyte is greatly improved and the impedance is reduced. In addition, due to the unique solid-state characteristics of the plastic crystal, the succinonitrile molecules fixed in the metal organic framework material will not react with the lithium metal negative electrode, which can greatly improve the electrochemical performance of the battery.
[0025] The battery containing the composite solid electrolyte membrane can have a higher discharge specific capacity. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0027] The composite solid electrolyte membrane and its preparation method and battery provided by the present invention are described in detail below.
[0028] The present invention provides a method for preparing a composite solid electrolyte membrane, comprising the following steps: mixing a first lithium salt with polyethylene oxide to obtain an electrolyte;
[0029] The electrolyte and the filler are mixed, and then annealed and pressed into a film to obtain a composite solid electrolyte membrane;
[0030] The preparation of the filler comprises: mixing succinonitrile, a second lithium salt and a metal organic framework material under a vacuum environment and then performing ultrasonic treatment.
[0031] The present application uses metal organic framework materials in the preparation process of composite solid electrolyte membranes to reduce the crystallinity of polymers and improve the mobility of polymer segments, thereby improving the conductivity of solid polymer electrolytes. At the same time, the unique molecular motion characteristics of the plastic molecule succinonitrile can make it have excellent motion characteristics, so it can be used as Li + However, it should be noted that simply mixing succinonitrile with the polymer electrolyte will greatly reduce the mechanical properties of the electrolyte. In addition, succinonitrile and lithium metal easily react, thereby deteriorating the electrochemical performance of the battery.
[0032] The present application first uses a metal organic framework material to confine the succinonitrile molecules inside its pores, so that the plasticizing effect of succinonitrile on the polymer chain segments is greatly reduced, which is beneficial to improving the mechanical properties of the polymer electrolyte. At the same time, as the content of the metal organic framework material increases, the metal organic framework material particles contact each other, prompting the succinonitrile in the pores of the metal organic framework material to form a connected three-dimensional network structure, so that the conductivity of the electrolyte is greatly improved and the impedance is reduced. In addition, due to the unique solid-state characteristics of the plastic crystal, the succinonitrile molecules fixed in the metal organic framework material will not react with the lithium metal negative electrode, which can greatly improve the electrochemical performance of the battery.
[0033] In some optional embodiments, the mass ratio of polyethylene oxide to the first lithium salt can be 100:15 to 100:50, such as 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45 or 100:50, or other values within the range of 100:15 to 100:50.
[0034] The first lithium salt may illustratively but not limitatively include at least one of LiTFSI, LiFSI, LiClO4, LiBF4, LiPF6, LDFOB and LiBOB.
[0035] In some optional embodiments, the mass ratio of electrolyte to filler can be 100:10 to 100:80, such as 100:10, 100:20, 100:30, 100:40, 100:50, 100:60, 100:70 or 100:80, or other values within the range of 100:10 to 100:80.
[0036] If the amount of filler is too little, it is not conducive to the construction of the lithium ion conduction network inside the composite electrolyte; if the amount of filler is too much, it is not conducive to maintaining the flexibility of the composite solid electrolyte.
[0037] In some optional embodiments, the annealing temperature may be 50°C to 80°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C, or other values within the range of 50°C to 80°C.
[0038] The annealing time may be 5 h to 10 h, such as 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc., or may be other values within the range of 5 h to 10 h.
[0039] By performing annealing under the above conditions, it is possible to promote sufficient and uniform mixing of the electrolyte and the filler.
[0040] In some optional embodiments, the pressing pressure can be 0.1 MPa to 5.0 MPa, such as 0.1 MPa, 0.5 MPa, 1 MPa, 2 MPa, 3 MPa, 4 MPa or 5 MPa, etc., and can be adjusted according to actual needs.
[0041] In some optional embodiments, the second lithium salt may illustratively but not limitatively include at least one of LiTFSI, LiFSI, LiCIO4, LiBF4, LiPF6, LDFOB and LiBOB.
[0042] The metal organic framework material may illustratively but not limitatively include at least one of MOF-818 and MOF-919.
[0043] In some optional embodiments, the mass ratio of the second lithium salt to succinonitrile can be 0.1:1 to 0.5:1, such as 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1 or 0.5:1, etc., or other values within the range of 0.1:1 to 0.5:1.
[0044] If the amount of succinonitrile is too little, it is not conducive to the filling of MOF materials; if the amount of succinonitrile is too much, it is not conducive to the improvement of ionic conductivity.
[0045] The ratio of the total mass of succinonitrile and the second lithium salt to the mass of the metal organic framework material can be 0.05:1 to 0.2:1, such as 0.05:1, 0.1:1, 0.15:1 or 0.2:1, or other values within the range of 0.05:1 to 0.2:1.
[0046] If the amount of metal organic framework material used is too small, it will not be conducive to fully absorbing the mixture of succinonitrile and the second lithium salt; if the amount of metal organic framework material used is too much, it will not be conducive to improving the pore filling rate of the MOF material, which will ultimately make it difficult to construct a composite electrolyte ion conduction network.
[0047] In some optional embodiments, the temperature of ultrasonic treatment can be 60°C to 200°C, such as 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, or other values within the range of 60°C to 200°C.
[0048] The time of ultrasonic treatment can be 0.1 h to 2 h, such as 0.1 h, 0.5 h, 1 h, 1.5 h or 2 h, etc., or other values within the range of 0.1 h to 2 h.
[0049] The ultrasonic treatment can promote the compounding of the mixture of succinonitrile and the second lithium salt with the metal organic framework material, so that the mixture of succinonitrile and the second lithium salt can effectively enter the porous structure of the metal organic framework material.
[0050] Furthermore, the material after ultrasonic treatment can be frozen and crushed. By first freezing the material after ultrasonic treatment (such as -40°C to -50°C), the subsequent crushing operation is more conducive to this temperature, and the material is not easy to agglomerate.
[0051] Correspondingly, the present invention also provides a composite solid electrolyte membrane, which is prepared by the above preparation method.
[0052] In some optional embodiments, the thickness of the composite solid electrolyte membrane may be 30 μm to 100 μm, such as 30 μm, 50 μm, 80 μm or 100 μm, etc., or may be other values within the range of 30 μm to 100 μm.
[0053] In addition, the present invention also provides a battery, which contains the composite solid electrolyte membrane.
[0054] The battery can have high ionic conductivity, mechanical properties and cycle stability.
[0055] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0056] Example 1
[0057] This embodiment provides a composite solid electrolyte membrane, and the preparation method thereof includes:
[0058] S1: preparing filler.
[0059] S11: mixing succinonitrile and a second lithium salt (LiPF6) to obtain a mixture;
[0060] S12: The mixture is mixed with a metal organic framework material (MOF-818) and placed in a vacuum environment, heated to 100° C. and subjected to ultrasonic treatment for 1 h; then frozen and ground.
[0061] The mass ratio of the second lithium salt to succinonitrile is 0.3:1; and the mass ratio of the total mass of succinonitrile and the second lithium salt to the mass of the metal organic framework material is 0.1:1.
[0062] S2: preparing a composite solid electrolyte membrane.
[0063] S21: mixing a first lithium salt (LiPF6) with polyethylene oxide to obtain an electrolyte;
[0064] S22: The electrolyte and the filler are mixed and kneaded, followed by annealing at 60° C. for 8 h, and then pressed into a film at 3 MPa to obtain a composite solid electrolyte membrane.
[0065] The mass ratio of polyethylene oxide to the first lithium salt is 100:30; and the mass ratio of the electrolyte to the filler is 100:10.
[0066] Example 2
[0067] The difference between this embodiment and embodiment 1 is that the mass ratio of electrolyte to filler is 100:20.
[0068] Example 3
[0069] The difference between this embodiment and embodiment 1 is that the mass ratio of electrolyte to filler is 100:30.
[0070] Example 4
[0071] The difference between this embodiment and embodiment 1 is that the mass ratio of electrolyte to filler is 100:40.
[0072] Example 5
[0073] The difference between this embodiment and embodiment 1 is that the mass ratio of electrolyte to filler is 100:50.
[0074] Example 6
[0075] The difference between this embodiment and embodiment 1 is that the mass ratio of electrolyte to filler is 100:60.
[0076] Example 7
[0077] The difference between this embodiment and embodiment 1 is that the mass ratio of electrolyte to filler is 100:70.
[0078] Example 8
[0079] The difference between this embodiment and embodiment 1 is that the mass ratio of electrolyte to filler is 100:80.
[0080] Example 9
[0081] This embodiment provides a composite solid electrolyte membrane, and the preparation method thereof includes:
[0082] S1: preparing filler.
[0083] S11: mixing succinonitrile and a second lithium salt (LiBF4) to obtain a mixture;
[0084] S12: The mixture was mixed with a metal organic framework material (MOF-818) and placed in a vacuum environment, heated to 60°C and ultrasonically treated for 2 hours; then frozen and ground.
[0085] The mass ratio of the second lithium salt to succinonitrile is 0.1:1; the mass ratio of the total mass of succinonitrile and the second lithium salt to the mass of the metal organic framework material is 0.05:1.
[0086] S2: preparing a composite solid electrolyte membrane.
[0087] S21: mixing a first lithium salt (LiBF4) with polyethylene oxide to obtain an electrolyte;
[0088] S22: The electrolyte and the filler are mixed and kneaded, followed by annealing at 50° C. for 10 h, and then pressed into a film at 5 MPa to obtain a composite solid electrolyte membrane.
[0089] The mass ratio of polyethylene oxide to the first lithium salt is 100:15; and the mass ratio of the electrolyte to the filler is 100:10.
[0090] Example 10
[0091] This embodiment provides a composite solid electrolyte membrane, and the preparation method thereof includes:
[0092] S1: preparing filler.
[0093] S11: mixing succinonitrile and a second lithium salt (LiClO4) to obtain a mixture;
[0094] S12: The mixture is mixed with a metal organic framework material (MOF-919) and placed in a vacuum environment, heated to 200° C. and ultrasonically treated for 0.1 h; then frozen and ground.
[0095] The mass ratio of the second lithium salt to the second succinonitrile is 0.5:1; and the mass ratio of the total mass of succinonitrile and the second lithium salt to the mass of the metal organic framework material is 0.2:1.
[0096] S2: preparing a composite solid electrolyte membrane.
[0097] S21: mixing a first lithium salt (LiClO4) with polyethylene oxide to obtain an electrolyte;
[0098] S22: The electrolyte and the filler are mixed and kneaded, followed by annealing at 80° C. for 5 h, and then pressed into a film at 0.1 MPa to obtain a composite solid electrolyte membrane.
[0099] The mass ratio of polyethylene oxide to the first lithium salt is 100:50; and the mass ratio of the electrolyte to the filler is 100:10.
[0100] Comparative Example 1
[0101] This comparative example provides a composite solid electrolyte membrane, the preparation method of which includes:
[0102] S1: mixing a first lithium salt (LiPF6) with polyethylene oxide to obtain an electrolyte;
[0103] S2: The electrolyte and succinonitrile are mixed and kneaded, followed by annealing at 60° C. for 8 h, and then pressed into a film at 3 MPa to obtain a composite solid electrolyte membrane.
[0104] The mass ratio of polyethylene oxide to the first lithium salt is 100:30; and the mass ratio of the electrolyte to succinonitrile is 100:10.
[0105] Comparative Example 2
[0106] The difference between this comparative example and comparative example 1 is that the mass ratio of the electrolyte to succinonitrile is 100:20.
[0107] Comparative Example 3
[0108] The difference between this comparative example and comparative example 1 is that the mass ratio of the electrolyte to succinonitrile is 100:30.
[0109] Comparative Example 4
[0110] The difference between this comparative example and comparative example 1 is that the mass ratio of the electrolyte to succinonitrile is 100:40.
[0111] Comparative Example 5
[0112] The difference between this comparative example and comparative example 1 is that the mass ratio of the electrolyte to succinonitrile is 100:50.
[0113] Comparative Example 6
[0114] The difference between this comparative example and comparative example 1 is that the mass ratio of electrolyte to succinonitrile is 100:60.
[0115] Comparative Example 7
[0116] The difference between this comparative example and comparative example 1 is that the mass ratio of the electrolyte to succinonitrile is 100:70.
[0117] Comparative Example 8
[0118] The difference between this comparative example and comparative example 1 is that the mass ratio of the electrolyte to succinonitrile is 100:80.
[0119] Comparative Example 9
[0120] The difference between this comparative example and Example 1 is that in S12, the ratio of the total mass of the second lithium salt and succinonitrile to the mass of the metal organic framework material is 0.4:1.
[0121] Comparative Example 10
[0122] The difference between this comparative example and Example 1 is that in S22, the mass ratio of the electrolyte to the filler is 100:5.
[0123] Comparative Example 11
[0124] The difference between this comparative example and Example 1 is that in S22, after the electrolyte and the filler are mixed and kneaded, no annealing treatment is performed and the film is directly pressed under 3 MPa.
[0125] Comparative Example 12
[0126] The difference between this comparative example and Example 1 is that MOF-808 is used in an equal amount to replace MOF-818.
[0127] Comparative Example 13
[0128] The difference between this comparative example and Example 1 is that MOF-818 is replaced by an equal amount of UIO-66.
[0129] Test example
[0130] The composite solid electrolyte membranes obtained in Examples 1 to 10 and Comparative Examples 1 to 13 were respectively assembled into button batteries according to the following method: the positive electrode plate (nickel-cobalt-manganese positive electrode plate) was placed in the center of the positive electrode shell, the cut composite solid electrolyte membrane was covered on the positive electrode plate, lithium metal was used as the negative electrode, placed on top of the electrolyte membrane, and then the gasket, spring sheet, and negative electrode shell were placed in sequence. After packaging, the button batteries were obtained for testing the discharge specific capacity. The test conditions were 25°C, 0.1C, and 3V to 4.3V.
[0131] In addition, the composite solid electrolyte membranes obtained in Examples 1 to 10 and Comparative Examples 1 to 13 were assembled into Li / Li batteries to test the deposition potential. The assembly process was the same as that of button batteries, except that the positive electrode was replaced with lithium metal.
[0132] The above test results are shown in Table 1.
[0133] Table 1 Test results
[0134]
[0135]
[0136] It can be seen from Table 1 that the composite solid electrolyte membrane prepared in the embodiment of the present invention has a lower deposition potential and a smaller impedance, and can enable the battery to have a higher discharge specific capacity.
[0137] In summary, the present invention first uses a metal organic framework material to confine the succinonitrile molecules inside its pores, so that the plasticizing effect of succinonitrile on the polymer chain segments is greatly reduced, which is beneficial to improving the mechanical properties of the polymer electrolyte. At the same time, as the content of the metal organic framework material increases, the metal organic framework material particles contact each other, prompting the succinonitrile in the pores of the metal organic framework material to form a connected three-dimensional network structure, so that the conductivity of the electrolyte is greatly improved. In addition, due to the unique solid-state characteristics of the plastic crystal, the succinonitrile molecules fixed in the metal organic framework material will not react with the lithium metal negative electrode, which can greatly improve the cycle stability of the battery.
[0138] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite solid electrolyte membrane, characterized in that: The following steps are involved: mixing a first lithium salt with polyethylene oxide to obtain an electrolyte; The electrolyte is mixed with a filler, and then annealed and pressed into a film to obtain a composite solid electrolyte membrane; The preparation of the filler comprises: mixing succinonitrile, a second lithium salt and a metal organic framework material and subjecting them to ultrasonic treatment in a vacuum environment.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the polyethylene oxide to the first lithium salt is 100:15 to 100:50; And / or, the mass ratio of the electrolyte to the filler is 100:10 to 100:
80.
3. The preparation method according to claim 1, characterized in that: The first lithium salt includes at least one of LiTFSI, LiFSI, LiCIO4, LiBF4, LiPF6, LDFOB and LiBOB.
4. The preparation method according to claim 1, characterized in that: The annealing temperature is 50°C to 80°C, and the annealing time is 5h to 10h.
5. The preparation method according to claim 1, characterized in that: The pressing pressure is 0.1MPa~5.0MPa.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The second lithium salt includes at least one of LiTFSI, LiFSI, LiClO4, LiBF4, LiPF6, LDFOB and LiBOB; And / or, the metal organic framework material includes at least one of MOF-818 and MOF-919.
7. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the second lithium salt to succinonitrile is 0.1:1 to 0.5:1; And / or, the ratio of the total mass of the succinonitrile and the second lithium salt to the mass of the metal organic framework material is 0.05:1 to 0.2:
1.
8. The preparation method according to any one of claims 1 to 5, characterized in that: The temperature of ultrasonic treatment is 60°C to 200°C, and the time of ultrasonic treatment is 0.1h to 2h.
9. A composite solid electrolyte membrane, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. A battery, characterized in that: The battery comprises the composite solid electrolyte membrane according to claim 9.
Citation Information
Patent Citations
Solid electrolyte membrane and solid-state battery comprising same
CN116057752A
Electrolyte and lithium secondary battery comprising same
KR1020150026717A